Development and Validation of a Stability Indicating HPTLC Method for Simultaneous Estimation of Telmisartan and Gallic Acid as per ICH Q1A (R2) - Pattanik, Swadesh Kumar; Pradhan, Kishanta Kumar (Indian Journal of Pharmaceutical Education and Research, 2024)
Background A simple, selective and sensitive HPTLC method was developed for simultaneous estimation of Telmisartan (TEL) and Gallic acid (GA). Oxidative stress produces hypertension, GA having antioxidative property that reduces ROS. TEL is safer angiotensin-1 receptor blocker. Objectives Literatures suggest antioxidant with cardiovascular drug produce synergistic effect. Materials and Methods The stationary-phase used was aluminium-backed silica gel 60F254 HPTLC plates (20 cm×10 cm, thickness-0.2 mm). The mobile-phase consisted of ethyl acetate: methanol: chloroform: acetic acid in the ratio of 4:2:2:0.2(v/v). Drugs were exposed to different stress conditions (Acid, Alkali, Oxidative, Thermal and Photolytic) for 8 hr, analysed at intervals of 2 hr. Detection and quantification were performed densitometrically (200-400 nm). Results Calibration plots showed good linear relation, with better correlation coefficient (R2). AUC of the drugs were between the concentration ranges of 200-1200 ng/spot. For GA, Rf value was 0.60, LOD-5.494 ng/spot, and LOQ-16.65 ng/spot. For TEL, Rf value was 0.67, LOD-19.877 ng/ spot, and LOQ-60.235 ng/spot. In alkaline solution, TEL degraded up to 12.5%, and GA degraded completely. Whereas, in oxidative environment 30% and 30.55% degradation of TEL and GA were noted. Conclusion Developed method was validated as per ICH guidelines, the performed forced degradation study will help for drug stability and formulation development.
Keywords: Method development and validation; Telmisartan; HPTLC; Gallic acid; Forced degradation study